Learning as a means for self-care of patients with intestinal elimination stoma - Diaz Carnero, Graciela Zoraida (2024)
The preparation of an intestinal elimination stoma implies a change in the body image and functioning of a person who, as a consequence, must relearn self-care in terms of elimination, whose behavior was learned since childhood. The aim of this trial is to analyze in depth whether learning is a determining factor or an instrumental means for the conscious (re)construction of self-care in patients with intestinal elimination stomas. For the analysis, the assumptions of Dorothea Orem's theory have been taken as a reference, who points out that self-care is a system of human self-regulation that requires the stimulation of cognitive behavioral processes through participatory learning. Likewise, it is postulated that each person learns at an individualized pace since this ability is determined by emotional intelligence, which we will have for the learning of practical skills. The loss of self-control, power and self-regulation due to the modification of body image and functioning seems to be a conditioning factor for learning, which is why it is essential to comprehensively address a series of internal and external conditions, where learning is a means to achieve the reconstruction of the self-care of the ostomized patient.